Optimization extraction process of Shenghua Decoction and evaluation of its analgesic effects - Zhonghui Pu; Lijuan Chen; Huaidan Liu; Jingzhu Deng; Li Li; Liang Xiong; Liuying Li (Results in Chemistry)
Shenghua Decoction (SHD) is a very famous formula that has been used for treating postpartum diseases in China. However, there has been no study published, to date, reporting the preparation process and analgesic effects of SHD. This study aimed to optimize the high-content SHD production process and investigate its analgesic activity. Taking the content of ferulic acid and senkyunolide I determined by HPLC as indexes, the effect on SHD of several extraction processing variables, including liquid–solid ratio, soaking time, decocting time and ethanol precipitation concentration, had been examined by using Box-Behnken design (BBD) with three levels and four factors were adopted for optimizing SHD extraction process, and the optimized conditions were further validated. The analgesic activity of SHD was assessed, based on mouse pain response to hot plate and intraperitoneally injected acetic acid. The optimized values of SHD extraction process variables were found to be 40 mL/g of liquid–solid ratio, 2 h of soaking time, 1.5 h of decocting time, 70 % of ethanol precipitation concentration. The optimum conditions led to maximal combined content of ferulic acid and senkyunolide I at 1.2336 mg/g averaged from three validation tests (RSD = 1.84 %, n = 3), 0.9347 mg/g for ferulic acid and 0.2989 mg/g for senkyunolide I, and the bias ratio was 1.82 % compared with the predicted value of 1.251 mg/g, indicating the experimental values obtained from the BBD model agreed with that of the predicted values.Analgesic activity results indicated that SHD at all doses significantly reduced the number of twists induced by glacial acetic acid dose-dependently, and prolonged latency of foot licking to varying degrees at every stage of mice hot-plate test. This study not only developed a rapid and sensitive process that was successfully utilized for extracting SHD, but also discovered SHD with analgesic activity, which provided helpful information for further study.